2022
DOI: 10.1136/bmjgh-2021-007747
|View full text |Cite|
|
Sign up to set email alerts
|

Cash, COVID-19 and aid cuts: a mixed-method impact evaluation among South Sudanese refugees registered in Kiryandongo settlement, Uganda

Abstract: ObjectivesIn this paper, we estimate the impact after 4–8 months of a large one-off unconditional cash transfer delivered to refugees during a time of dual shocks: the COVID-19 pandemic and cuts to monthly aid. We focus on four key outcomes: (1) health-seeking behaviour; (2) COVID-19 specific preventive health practices; (3) food security and (4) psychological well-being.MethodsWe use both quantitative and qualitative data to understand the impact of a cash transfer in this context. Quantitatively, we use a ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Studies of cash transfer programs, while heterogeneous in quality and findings, suggest that such interventions may have positive impacts on health [ 9 13 ]. Cash transfer programs have been implemented across the globe in response to the COVID-19 pandemic, with international studies finding effects on food security and access to healthcare [ 14 16 ]. In the USA, government and private philanthropy deployed various cash transfer programs during the pandemic, [ 17 – 19 ] but it is rarer for a health system to be explicitly involved in the design and implementation of such a program [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of cash transfer programs, while heterogeneous in quality and findings, suggest that such interventions may have positive impacts on health [ 9 13 ]. Cash transfer programs have been implemented across the globe in response to the COVID-19 pandemic, with international studies finding effects on food security and access to healthcare [ 14 16 ]. In the USA, government and private philanthropy deployed various cash transfer programs during the pandemic, [ 17 – 19 ] but it is rarer for a health system to be explicitly involved in the design and implementation of such a program [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cash-based interventions have the potential to influence a range of public health outcomes, but evidence on their impacts is mixed in low-income and middle-income settings where aid is given (13-15). Evaluations of the World Food Program's delivery of cash assistance in conjunction with food parcels in refugee camps have revealed that offering refugees the choice to receive cash in lieu of food parcels yield dietary improvements, higher diet diversity, increased financial stability and food security, and greater feelings of self-sufficiency (11,12,16,17). Multiple evaluations of cash-based programs have also demonstrated improvements in height, HAZ scores, and newborn birth weight in addition to positive pregnancy outcomes across age groups and geographical contexts (18,19).…”
Section: Impacts Of Cash-based Interventionsmentioning
confidence: 99%
“…Other non-nutritional impacts identified in evaluations of cash-based interventions in refugee settings include improved psychological wellbeing, which has been associated with food security in observational studies (16,21). Empirical evidence on the impact of cash-based interventions on other health outcomes is sparse; however, simulation studies have not supported that replacing traditional food assistance with cash led to meaningful changes in a range of chronic diseases and other health outcomes.…”
Section: Impacts Of Cash-based Interventionsmentioning
confidence: 99%
“…Unconditional cash transfer has been effective in several countries affected by humanitarian catastrophes but not utilized for alleviating planned, non-emergent surgical procedures in LMIC. Stein et al [ 11 ] used both quantitative and qualitative data to understand the impact of unconditional cash transfer to refugees in the setting of the COVID-19 pandemic and subsequent cuts to monthly aid. Through telephonic surveys in 1,200 households, the authors investigated the effect of these cash transfers on COVID-19 specific preventative health practices, food security and psychological well-being.…”
Section: Unconditional Cash Transfer To Reduce Unmet Surgical Needsmentioning
confidence: 99%